Association Between Severe Vitamin D Deficiency, Lung Function and Asthma Control - CEYHAN, BERRİN; BALCAN, MEHMET BARAN (ELSEVIER ESPANA SLU, 2017)
Introduction: To examine the relationship between severe vitamin D deficiency, asthma control, and pulmonary function in Turkish adults with asthma. Methods: One hundred six asthmatic patients underwent pulmonary function tests skin prick test, peripheral blood eosinophil counts, IgE, body mass index and vitamin D levels were determined. Patients were divided into 2 subgroups according to vitamin D levels (vitamin D level < 10 ng/ml and vitamin D level >= 10 ng/ml). Asthma control tests were performed. Results: The mean age of subgroup I (vitamin D level < 10) was 37 +/- 10 and the mean age of subgroup II (vitamin D level >= 10 ng/ml) was 34 +/- 8. Sixty-six percent of patients had severe vitamin D deficiency (vitamin D level < 10 ng/m1). There was a significant trend towards lower absolute FEV1 (L) values in patients with lower vitamin D levels (P=.001). Asthma control test scores were significantly low in the severe deficiency group than the other group (P=.02). There were a greater number of patients with uncontrolled asthma (asthma control test scores < 20) in the severe vitamin D deficiency group (P=.040). Patients with severe vitamin D deficiency had a higher usage of inhaled corticosteroids than the group without severe vitamin D deficiency (P=.015). There was a significant trend towards lower absolute FEV1 (L) (P=.005, r =.272) values in patients with lower vitamin D levels. Vitamin D levels were inversely related with body mass index (P=.046). Conclusion: The incidence of severe vitamin D deficiency was high in adult Turkish asthmatics. In addition,lower vitamin D levels were associated with poor asthma control and decreased pulmonary function.(C) 2016 SEPAR. Published by Elsevier Espana, S.L.U. All rights reserved.
Keywords: Asthma control; FEV1; Pulmonary function; Severe vitamin D deficiency; SERUM 25-HYDROXYVITAMIN D; SMOOTH-MUSCLE-CELLS; 3RD NATIONAL-HEALTH; CHILDHOOD ASTHMA; D INSUFFICIENCY; ADULTS; DISEASE